Use of a Fascia Lata Autograft to Reconstruct a Large Triceps Tendon Defect After En-Bloc Resection of a Soft-Tissue Sarcoma: A Case Report. Issue 1 (January 2020) - Clancy, Rachel; Lim, Zachary; Ravinsky, Robert A.; O'Neill, Anne; Ferguson, Peter; Wunder, Jay
Abstract : Case: In this report, we present the case of a patient undergoing en-bloc resection of a large triceps soft-tissue sarcoma, requiring reconstruction of the triceps tendon including its distal insertion. We describe a surgical technique using fascia lata (FL) autograft to reconstruct the patient's extensor mechanism with long-term follow-up and functional results. Conclusions: FL autograft is a viable option for reconstruction of large tendinous defects. It is simple and straightforward to harvest, inexpensive when compared with alternatives, with many potential applications.